Problemy budowy strategii rozwoju województw i powiatów na tle dokumentów programowych rządu - Pancer-Cybulska, Ewa (Problems with construction of voivodships and powiats strategies of development vs. government programme documents, 2006)
The EU cohesion policy planned for years 2007-13 should include local society experience gained in pre-accession period and one-year membership in the EU. Launching regional operational programme instead of the Integrated Regional Operational Programme (2004-2006) is connected with decentralization of system of regional policy. The most difficult problem facing authorities due to setting relations between voivodship, powiat and gmina local self-governments and other subjects involved in developing strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 95-104